A simplified multi-performance approach to life-cycle assessment of steel structures. (October 2020) - Romano, Elvira; Cascini, Lucrezia; D'Aniello, Mario; Portioli, Francesco; Landolfo, Raffaele
Abstract: This paper presents an application of a simplified assessment approach to steel structures which takes into account sustainability requirements. The proposed approach is based on a time-dependent, multi-performance-based design methodology. The simplified procedure is organized in three main steps concerning the environmental conceptual design, the ordinary structural design and the life-cycle analysis devoted to defining service life scenarios in order to assess the structural, economic and environmental performances of structures during their entire life-cycle. Three different seismic-resistant steel structural typologies are designed for a multi-storey residential building and compared in terms of sustainability. Those comprise Moment Resisting Frames (MRF), Concentrically Braced Frames (CBF) with removable Chevron braces and Eccentrically Braced Frames (EBF) with removable shear links. The structural, environmental and economic performances of the three examined design options are assessed and compared in order to evaluate their sustainable potentialities and criticalities for two design scenarios, namely an ordinary condition characterized by an expected deterioration and an exceptional case in which a seismic event hits the structures during their service life.